Five‐year refractive changes in a rural Chinese adult population and its related factors: the Handan Eye Study. (17th April 2018) - Li, Shi‐Ming; Lin, Caixia; Wan, Yue; Cao, Kai; Hao, Jie; Zhang, Ye; Hu, Ailian; Wu, Jian; Friedman, David S; Wang, Ningli
Abstract: Importance: Provision of refractive changes is important to predict eye care needs for aging population. Background: To provide 5‐year refractive changes in a rural Chinese adult population. Design: Population‐based longitudinal study. Participants: At baseline, 6830 subjects aged 30+ years took part in the Handan Eye Study. A total of 5394 of the 6323 survivors (85.3%) participated in the 5‐year follow‐up. Methods: Ocular examinations including standardized refraction were performed according to the same protocol at both baseline and follow‐up. Main Outcome Measures: Change in spherical equivalent (SE; sphere + 1/2 cylinder) and astigmatism. Results: A total of 3970 right eyes were available for refraction analysis. The 5‐year change in SE for all subjects was +0.17 diopters (D), and was −0.21D, +0.14D, +0.40D and +0.08D for subjects aged 30–39, 40–49, 50–59, and 60–69 years, respectively. By binary regression analysis, myopic shift was associated with severe nuclear opacity, longer axil length, diabetes and large change of lens power, while hyperopic shift was associated with older age and ocular hypertension at baseline. There was a mean change of 0.18D in the against‐the‐rule astigmatism. Conclusions and Relevance: There was a myopic shift for those 30–39 years old and a hyperopic shift from 40 to 69 years old in a rural Chinese adult population. Those with severe nuclear opacity, longer axil length, diabetes and large change of lens power tended to have a myopic shift, while those being older and having ocular hypertension at baseline were prone to have a hyperopic shift. There was also an increase in against‐the‐rule astigmatism in this population.